(untitled) (Razão e Fé, 2026)
The article approaches the Theology of Grace from Sacred Scripture in the light of bibliographical research. The intention is to go through the itinerary of the elaboration of the theology on divine grace, its relationship with nature and freedom, seeking to understand the gracious action of God in creation, as well as in the election of the people of Israel, where God manifests his grace and mercy acting in their favor. The term cháris in the New Testament finds its relevance in the grace lived in the community of the Apostles.